Mantoux test results and BCG vaccination status in TB-exposed children - Fadilah Harahap; Ridwan M. Daulay; Muhammad Ali; Wisman Dalimunthe; Rini Savitri Daulay (Indonesian Pediatric Society, 2015)
Background Tuberculosis (TB) infection is highly prevalent in Indonesia. The source of transmission of TB to a child is usually via an adult with sputum smear-positive pulmonary tuberculosis. The Mantoux test is a diagnostic tool for tuberculosis infection. The BCG vaccine has been used for the prevention of TB, but its efficacy is still debated. Objective To assess for an association between Mantoux test results and BCG vaccination in children who had contact with adult pulmonary tuberculosis and to assess for differences in Mantoux test induration with regards to nutritional status, age, type of TB contact, and time duration since BCG vaccination in BCG-vaccinated and BCG-unvaccinated children. Methods A cross-sectional study was conducted in FebruaryMarch 2011 on infants and children (aged 3 months to five years), who had household contact with adult pulmonary TB. We performed tuberculin (Mantoux) skin tests to detect TB infection in the children. Subjects were consisted of two groups: BCG-vaccinated and BCG-unvaccinated. Results Subjects were 100 children (50 BCG-vaccinated and 50 BCG-unvaccinated subjects). Positive Mantoux test results were observed in 9 vaccinated subjects and 33 unvaccinated subjects. The mean diameters of induration in the vaccinated and unvaccinated groups were 7.6 mm and 9.6 mm, respectively (95%CI of difference -4.25 to 0.20; P=0.074). In children who had household contact with sputum smear-positive adult pulmonary TB, BCG vaccination was a protective factor against TB infection, with an odds ratio (OR) of 0.113 (95%CI 0.045 to 0.286; P=0.0001). There were no significant differences in Mantoux test induration associated with nutritional status, age, type of TB contact, and duration since BCG vaccination, between the two groups. Conclusion BCG vaccination has a protective effect on TBexposed children, based on Mantoux test results. However, there are no differences in Mantoux test induration associated withÂ nutritional status, age, type of TB contact, or duration since BCG vaccination, between the BCG-vaccinated and BCGunvaccinated groups.